A cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst and its preparation method and application

By introducing cerium oxide into the carbon-coated nickel-based catalyst, a cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst was prepared, which solved the problem of low yield of C4+ high-carbon alcohol in the synthesis of high-carbon alcohols, and achieved efficient production of high-carbon alcohols.

CN119140105BActive Publication Date: 2025-04-11GUANGDONG UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411446492.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-04-11
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In the process of synthesis of high-carbon alcohols with low yields of C4+ high-carbon alcohols in the aqueous phase small molecule, it is difficult to effectively overcome the sintering problem.

Method used

A cerium oxide-supported carbon coated nickel-based anti-sintering catalyst was used to add cerium oxide to a homogeneous solution containing soluble nickel salt and organic acid, and then stir, dry and calcined to prepare a stable catalyst.

Benefits of technology

The catalyst's anti-sintering ability is improved, the yield of high carbon alcohol is enhanced, the properties of the reaction interface are optimized, and the ethanol coupling reaction is promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140105B_ABST
    Figure CN119140105B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of catalyst technology, and in particular, to a cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst, and a preparation method and application thereof. The present invention adds cerium oxide to a homogeneous solution containing a soluble nickel salt and an organic acid, and obtains a precursor through stirring and drying; the precursor is subjected to a calcination treatment to obtain a cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst. Specific CeO2 is introduced to stabilize active metal particles (nickel) to prevent them from agglomerating, and to enhance the anti-sintering ability of the catalyst, effectively preventing the occurrence of side reactions, and increasing the yield of the target product. At the same time, the synergistic effect of CeO2 and metallic nickel can adjust the electronic properties of the metal, promote the process of hydrogenation and dehydrogenation, change the properties of the reaction interface, and guide the reactants to be adsorbed and converted in a more favorable manner, thereby achieving an increase in the yield of higher alcohols.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst and a preparation method and application thereof. Background Art

[0002] High-carbon alcohols play an important role in the chemical, pharmaceutical, fragrance and food industries. As solvents and surfactants, high-carbon alcohols can effectively improve product stability and solubility. In addition, high-carbon alcohols are also used to synthesize a variety of chemicals and participate in the production process as intermediates. For example, hexanol and heptanol are often used in the synthesis of fragrances and plasticizers.

[0003] At present, the research on high-carbon alcohols in the field of biofuels is gradually increasing. Compared with traditional petroleum-based fuels, bio-based high-carbon alcohols have lower environmental impact and better renewability. The production of high-carbon alcohols from renewable resources such as vegetable oils and sugars through bioconversion processes such as fermentation and esterification has become an important research direction for sustainable development. Studies have shown that high-carbon alcohols, as biofuel additives, can improve combustion characteristics and reduce greenhouse gas emissions.

[0004] The synthesis method of high-carbon alcohols is also a current research focus. Among them, the Guerbet aldol condensation method can achieve carbon chain growth to prepare higher alcohols through carbon-carbon coupling of small molecule alcohols. This process mainly consists of three parts. The first step is that low-carbon alcohols such as methanol or ethanol undergo dehydrogenation reaction at the active site to generate corresponding aldehydes; the second step, the aldehydes generated in the first step will undergo aldol condensation reaction at the alkaline site, and a molecule of water will be lost during the reaction to generate unsaturated aldehydes; finally, the unsaturated aldehydes are hydrogenated to generate the corresponding high-carbon alcohols with high carbon numbers. The most critical part of this method is the dehydrogenation and hydrogenation reactions in the first and third steps, which require the catalyst to have corresponding metal active centers. Therefore, most of the current catalytic systems use organic metals and transition noble metals such as Ru, Rh, Pa, Os, Ir and Pt, but still face the problems of difficult separation and recovery and high cost of noble metal catalytic applications.

[0005] Nickel is a transition metal element that is relatively abundant in the earth's crust and is one of the precious metal substitutes. The Chinese invention patent with publication number CN117138788A discloses a carbon-coated nickel Ni@C catalyst for catalyzing CO methanation reaction. Under high temperature conditions, the carbon layer may degrade or fall off, resulting in exposure of nickel particles and sintering, which will cause methanation reaction of small molecule alcohols, which is not conducive to the occurrence of Guerbet carbon-carbon condensation reaction.

[0006] How to overcome the problem of low yield (25.0%) of C4+ higher carbon alcohols when the existing carbon-coated nickel-based catalyst is used for the aqueous phase small molecule synthesis of higher carbon alcohols has become a research focus for those skilled in the art. Summary of the invention

[0007] The purpose of the present invention is to provide a cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.

[0008] To achieve the above object, the present invention provides the following solutions:

[0009] One of the technical solutions of the present invention is to provide a method for preparing a cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst, the steps comprising:

[0010] Cerium oxide (CeO2) is added to a homogeneous solution containing a soluble nickel salt and an organic acid, and the mixture is stirred and dried to obtain a precursor;

[0011] The precursor is calcined to obtain a cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst.

[0012] Furthermore, the organic acid includes citric acid, malic acid, tartaric acid, oxalic acid or pyruvic acid, preferably citric acid.

[0013] Organic acids play multiple roles in the preparation of carbon-coated nickel-based catalysts. The presence of organic acids can regulate the morphology and structure of the precursor during the pyrolysis process. During heat treatment or pyrolysis, organic acids can be used as a carbon source to generate carbonaceous materials through high-temperature decomposition. These carbonaceous materials form a coating layer on the surface of the metal nickel particles, which plays a role in protecting and stabilizing the metal nickel particles. During the pyrolysis process, organic acids decompose to generate gases such as CO2 and CO, which can provide a partial reducing atmosphere for the reduction of nickel. Especially in the carbon coating process, the decomposition products of organic acids help to create certain reducing conditions in the local environment, thereby promoting the reduction of nickel ions and obtaining metallic nickel (Ni 0 ) nanoparticles.

[0014] The synergistic effect between CeO2 and metals (such as nickel) can significantly regulate the electronic properties of metals, thereby affecting catalytic performance. CeO2 can change the electron density of metals through charge transfer with metals. For example, CeO2 has strong reduction-oxidation characteristics and can inject electrons into or extract electrons from nickel, thereby changing the d electron state density of nickel. This change in electron density will affect the adsorption strength of nickel on reactants, the reaction energy barrier, and the stability of intermediates, thereby regulating catalytic activity and selectivity. At the same time, because CeO2 has strong redox properties, it can provide or absorb oxygen species during the reaction process and participate in the catalytic cycle. This redox process can synergize with nickel metal to improve the activity of the catalyst in the Guerbet reaction. The electronic and geometric structures at the interface between metals and CeO2 are usually very different from those of metals or CeO2 alone, and can produce new catalytic active sites. Structural adjustments at the nickel-CeO2 interface can affect the adsorption pattern of reactants, especially in catalytic hydrogenation or dehydrogenation reactions, where CeO2 can optimize the catalytic path by changing the electronic properties of nickel.

[0015] Furthermore, the cerium oxide is nano-scale cerium oxide.

[0016] Furthermore, the homogeneous solution is obtained by adding the soluble nickel salt and the organic acid into water and stirring the water.

[0017] Preferably, the molar ratio of the soluble nickel salt to the organic acid is 1 to 4:4, more preferably 2:4.

[0018] Furthermore, the molar ratio of the cerium oxide to the soluble nickel salt is 4:1-4, preferably 4:2.

[0019] Furthermore, the stirring is carried out at 40-100° C. for 1-2 hours.

[0020] Furthermore, the calcination treatment is carried out at a temperature of 400 to 600° C. and for a time of 1 to 3 hours.

[0021] Preferably, the calcination temperature is 550°C.

[0022] Furthermore, the calcination process is performed under an inert atmosphere.

[0023] Conventional soluble nickel salts in the art can be used in the present invention. Furthermore, the nickel salt is preferably nickel nitrate.

[0024] The present invention introduces specific CeO2 to stabilize active metal particles (nickel) to prevent them from agglomerating, and enhances the anti-sintering ability of the catalyst, effectively preventing the occurrence of side reactions, and increasing the yield of the target product. At the same time, the synergistic effect of CeO2 and metal nickel can adjust the electronic properties of the metal, promote the process of hydrogenation and dehydrogenation, change the properties of the reaction interface, guide the reactants to be adsorbed and converted in a more favorable manner, and thus achieve an increase in the yield of higher alcohols.

[0025] The second technical solution of the present invention is to provide a cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst prepared by the above preparation method.

[0026] The third technical solution of the present invention is to provide an application of the above-mentioned cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst in catalyzing the aqueous phase synthesis of high-carbon alcohols from small molecule alcohols.

[0027] Furthermore, the small molecule alcohol is ethanol; and the high carbon alcohol is an alcohol with 4 to 16 carbon atoms.

[0028] The fourth technical solution of the present invention is to provide a method for synthesizing high-carbon alcohols from small-molecule alcohols in aqueous phase, wherein the method is based on the above-mentioned cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst and homogeneous base sodium hydroxide co-catalyzing the carbon-carbon coupling reaction of ethanol to generate high-carbon alcohols, and the steps include:

[0029] The cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst, sodium hydroxide, a mixture of ethanol and water are used as reaction substrates and placed in a reactor. After leak detection, the air in the reactor is replaced with high-purity hydrogen. The reaction is continued for 24 hours at a temperature of 190°C, an initial pressure of 0.1MPa, and a stirring speed of 1000-1500rpm. After the reaction, the substrate spontaneously separates into two phases of oil and water, and the oil phase obtained after centrifugal separation is high-carbon alcohol.

[0030] Furthermore, the mass ratio of the cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst, sodium hydroxide, ethanol and water is 1:1:(10-40):(10-40).

[0031] In the reaction system of synthesizing high-carbon alcohols from small-molecule alcohols in aqueous phase, water is mainly used as a solvent to dissolve sodium hydroxide, and sodium hydroxide is used as the base site to catalyze the aldol condensation process, that is, the process of CC coupling after the initial ethanol dehydrogenation. The aldol reaction easily occurs on a basic catalyst and may be carried out through a surface enolate. Enolates act as nucleophiles and attack other aldehydes or ketones present in the system. In this reaction process, the CC bond is cleaved to produce carbon dioxide, which then reacts with sodium hydroxide to produce sodium carbonate and sodium bicarbonate. Therefore, it is necessary to add sufficient sodium hydroxide and solvent water to the reaction to increase the yield of alcohol. The Guerbet reaction is a complex reaction network involving dehydrogenation, condensation and rearrangement, and NaOH, as an alkaline catalyst, can effectively promote the ethanol dehydrogenation and aldol condensation of aldehydes in these steps. Compared with stronger or weaker bases, NaOH can maintain good catalytic activity and high product selectivity, especially in the process of generating high-carbon alcohols; common side reactions in the Guerbet reaction include decomposition of alcohols, excessive condensation, etc. Although NaOH has strong alkalinity, the incidence of side reactions is low compared with some stronger bases (such as KOH), especially under high temperature conditions. NaOH has good solubility in ethanol and can be evenly distributed in the reaction system as a homogeneous base catalyst to ensure uniform reaction. At the same time, NaOH is a cheap, easily available and easy to handle chemical, which makes it practical and economical in industrial production. In the design of some Guerbet reactions, sodium hydroxide is used to avoid the potential impact of introducing metal ions (such as potassium ions or lithium ions) on the reaction selectivity. These ions may have complex interactions with reactants or catalysts at high temperatures, affecting the yield and selectivity of the final product.

[0032] The present invention discloses the following technical effects:

[0033] The cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst CeO2 carrier prepared by the present invention can help stabilize metal particles (nickel), prevent their agglomeration, enhance the anti-sintering ability of the catalyst, optimize the properties of the reaction interface, guide the reactants to be adsorbed and converted in a more favorable manner, optimize the reaction path, thereby strengthening the mass transfer of reactants in the process of preparing high-carbon alcohols by ethanol coupling, promoting the secondary growth of the carbon chain, and increasing the yield of high-carbon alcohols.

[0034] The cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst prepared by the invention is a heterogeneous catalyst and is easy to separate, recycle and reuse in the process of preparing high-carbon alcohols. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 XRD patterns of Ni@C-CeO2 and Ni@C;

[0037] Figure 2 TEM image of the cerium oxide supported carbon coated nickel-based anti-sintering catalyst prepared in Example 1;

[0038] Figure 3 TEM image of the cerium oxide supported carbon coated nickel-based anti-sintering catalyst prepared in Example 5;

[0039] Figure 4 This is the TEM image of the cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst prepared in Example 8. DETAILED DESCRIPTION

[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0041] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0045] Example 1

[0046] The preparation steps of cerium oxide supported carbon coated nickel-based anti-sintering catalyst are as follows:

[0047] S1. Add soluble nickel salt (nickel nitrate) and citric acid into deionized water in a molar ratio of 3:4, and stir to form a homogeneous solution;

[0048] S2, adding cerium oxide to the homogeneous solution, stirring at 50° C. for 2 hours, and drying to obtain a precursor, wherein the molar ratio of the soluble nickel salt to the cerium oxide is 3:4;

[0049] S3. The precursor was calcined at 550°C for 2 h in a nitrogen atmosphere to obtain a cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst, which was recorded as Ni@C-CeO2.

[0050] Example 2

[0051] The preparation steps of cerium oxide supported carbon coated nickel-based anti-sintering catalyst are as follows:

[0052] S1. Add soluble nickel salt (nickel nitrate) and citric acid into deionized water in a molar ratio of 1:4, and stir to form a homogeneous solution;

[0053] S2, adding cerium oxide to the homogeneous solution, stirring at 50° C. for 2 hours, and drying to obtain a precursor, wherein the molar ratio of the soluble nickel salt to the cerium oxide is 1:4;

[0054] S3. The precursor is calcined at 550° C. for 2 h in a nitrogen atmosphere to obtain a cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst.

[0055] Example 3

[0056] The preparation steps of cerium oxide supported carbon coated nickel-based anti-sintering catalyst are as follows:

[0057] S1. Add soluble nickel salt (nickel nitrate) and citric acid into deionized water in a molar ratio of 2:4, and stir to form a homogeneous solution;

[0058] S2, adding cerium oxide to the homogeneous solution, stirring at 50° C. for 2 hours, and drying to obtain a precursor, wherein the molar ratio of the soluble nickel salt to the cerium oxide is 2:4;

[0059] S3. The precursor is calcined at 550° C. for 2 h in a nitrogen atmosphere to obtain a cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst.

[0060] Example 4

[0061] The preparation steps of cerium oxide supported carbon coated nickel-based anti-sintering catalyst are as follows:

[0062] S1. Add soluble nickel salt (nickel nitrate) and citric acid into deionized water in a molar ratio of 4:4, and stir to form a homogeneous solution;

[0063] S2, adding cerium oxide to the homogeneous solution, stirring at 50° C. for 2 hours, and drying to obtain a precursor, wherein the molar ratio of the soluble nickel salt to the cerium oxide is 4:4;

[0064] S3. The precursor is calcined at 550° C. for 2 h in a nitrogen atmosphere to obtain a cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst.

[0065] Example 5

[0066] Compared with Example 1, the only difference is that the calcination temperature in step S3 is 400°C.

[0067] Example 6

[0068] Compared with Example 1, the only difference is that the calcination temperature in step S3 is 450°C.

[0069] Example 7

[0070] Compared with Example 1, the only difference is that the calcination temperature in step S3 is 500°C.

[0071] Example 8

[0072] Compared with Example 1, the only difference is that the calcination temperature in step S3 is 600°C.

[0073] Comparative Example 1

[0074] The preparation steps of carbon-coated nickel-based catalyst are as follows:

[0075] S1, dissolving nickel nitrate and citric acid in a molar ratio of 3:4 in deionized water and stirring to form a homogeneous solution;

[0076] S2, stirring the homogenized solution at 80° C. for 12 h, and drying to obtain a precursor;

[0077] S3. calcining the precursor at 550° C. for 2 h in a nitrogen atmosphere to obtain a carbon-coated nickel-based catalyst, denoted as Ni@C.

[0078] Test example

[0079] The catalysts prepared in Examples 1 to 8 and Comparative Example 1 were placed in a high-pressure reactor to catalyze the carbon-carbon coupling reaction of ethanol with a homogeneous base to generate higher alcohols. The specific steps are as follows:

[0080] S1. Add 0.5 g of catalyst, 0.5 g of NaOH, 10 g of ethanol and 10 g of water into a high-pressure reactor. After leak detection, replace the air in the reactor with high-purity hydrogen.

[0081] S2, at a reaction temperature of 190° C., an initial pressure of 0.1 MPa and a stirring speed of 1500 rpm, the reaction was continued for 12 hours. After the reaction was completed, the reaction system was cooled to room temperature, the gas phase was collected using an air bag, and the liquid phase product in the reactor was taken out;

[0082] S3, liquid phase and solid phase catalyst are obtained by centrifugation and filtration separation, and the liquid phase will naturally separate into oil phase and water phase after standing;

[0083] The S4 gas phase product, water phase and oil phase were qualitatively and quantitatively analyzed by gas chromatography. The results showed that the main product of the oil phase was C4+ high carbon alcohol. The analysis showed that C4+ high carbon alcohol was mainly composed of alcohols with 4 to 16 carbon atoms. The analysis results are shown in Table 1.

[0084] Table 1

[0085]

[0086]

[0087] From the results in Table 1, it can be seen that when the CeO2-loaded carbon-coated nickel-based anti-sintering catalysts prepared in Examples 1 to 8 by changing the ratio of soluble nickel salt to citric acid and CeO2 and the carbonization temperature are used for the preparation of high-carbon alcohols by carbon-carbon coupling of ethanol, it can be seen that the catalyst prepared in Example 1 has the best performance, and the ethanol conversion rate, organic phase product yield, liquid phase product C4+ high-carbon alcohol selectivity, and C4+ high-carbon alcohol yield all reach a relatively high level; while in Comparative Example 1, since no CeO2 is added, the catalyst carrier prepared cannot promote the dispersion of the active component nickel, resulting in a low yield of C4+ high-carbon alcohols, ethanol conversion, and organic phase yield.

[0088] Figure 1The XRD diagrams of Ni@C-CeO2 and Ni@C show that Ni@C-CeO2 has an obvious CeO2 diffraction peak with a sharp peak shape, while the peak intensity of the elemental Ni peak is small and wide, indicating that the active component nickel on Ni@C-CeO2 is successfully loaded on CeO2 and has good dispersion, while Ni@C does not have a CeO2 diffraction peak, and the elemental Ni peak shape is sharp and has good crystallinity. At the same time, the XRD diagrams of the cerium oxide-loaded carbon-coated nickel-based anti-sintering catalysts obtained in Examples 2 to 8 all show C, CeO2 and elemental Ni peaks, which are not listed one by one here.

[0089] Figure 2 TEM image of the cerium oxide supported carbon coated nickel-based anti-sintering catalyst prepared in Example 1; Figure 3 TEM image of the cerium oxide supported carbon coated nickel-based anti-sintering catalyst prepared in Example 5; Figure 4 This is a TEM image of the cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst prepared in Example 8. Examples 1, 5 and 8 are catalysts prepared under different calcination temperature conditions. It can be seen from the figure that the carbonization temperature has a significant effect on the structure of the catalyst. Among them, the catalyst particles are most evenly distributed at a carbonization temperature of 550°C. Too high or too low a temperature will lead to sintering and agglomeration of the metal phase in the catalyst, resulting in uneven particle dispersion and affecting the catalytic activity, which corresponds to the results in Table 1.

[0090] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst for catalyzing the aqueous phase synthesis of high-carbon alcohols from small molecule alcohols, characterized in that the steps include: adding cerium oxide to a homogeneous solution containing a soluble nickel salt and an organic acid, stirring and drying, to obtain a precursor; calcining the precursor to obtain a cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst; The organic acid includes citric acid, malic acid, tartaric acid, oxalic acid or pyruvic acid; the cerium oxide is nano-scale cerium oxide; the homogeneous solution is obtained by adding the soluble nickel salt and the organic acid into water and stirring; the molar ratio of the soluble nickel salt to the organic acid is 1 to 4:4; The molar ratio of the cerium oxide to the soluble nickel salt is 4:1-4; The calcination treatment is carried out at a temperature of 400 to 600° C. and for a time of 1 to 3 hours.

2. The preparation method according to claim 1, characterized in that The stirring is carried out at 40-100° C. for 1-2 hours.

3. The preparation method according to claim 1, characterized in that: The calcination treatment is performed under an inert atmosphere.

4. The cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst prepared by the preparation method according to claim 1.

5. Use of the cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst as claimed in claim 4 in catalyzing the aqueous phase synthesis of higher carbon alcohols from small molecule alcohols.

6. A method for synthesizing higher alcohols from small molecule alcohols in aqueous phase, characterized in that: The method is based on the cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst according to claim 4 and the homogeneous base sodium hydroxide co-catalyzing the carbon-carbon coupling reaction of ethanol to produce higher alcohols, and the steps include: The cerium oxide-loaded carbon-coated nickel-based anti-sintering catalyst, sodium hydroxide, a mixture of ethanol and water are used as reaction substrates and placed in a reactor. After leak detection, the air in the reactor is replaced with high-purity hydrogen. The reaction is continued for 24 hours at a temperature of 190°C, an initial pressure of 0.1MPa, and a stirring speed of 1000-1500rpm. After the reaction, the substrate spontaneously separates into two phases of oil and water, and the oil phase obtained after centrifugal separation is high-carbon alcohol.

7. The method according to claim 6, characterized in that The mass ratio of the cerium oxide-supported carbon-coated nickel-based anti-sintering catalyst, sodium hydroxide, ethanol and water is 1:1:(10-40):(10-40).

Citation Information

Patent Citations

  • Ni-coated C catalyst, preparation method thereof and CO2 methanation reaction catalyzed by nickel catalyst

    CN117138788A

  • High-dispersion film-shaped carbon-coated nickel catalyst as well as preparation method and application thereof

    CN115318296A